'Find-think-write-publish' : Lean thinking in scientific paper writing - Björnfot, Anders; Johnsson, Helena; Simonsson, Peter (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2012)
Construction research supports long-term development of the construction industry and the society. Thus it is important to evaluate research against existing knowledge and to constantly develop new knowledge. The main mechanism for doing so is publishing scientific papers. In Sweden, praxis has developed that a Ph.D. consists of a handful of scientific papers. The average time period for a Ph.D. is five years after which the funding situation changes drastically. Previously, the duration of Ph.D. studies at Luleå University of Technology, Sweden often exceeded the planned five years, disrupting the flow of Ph.D. examinations. To increase awareness and interest in paper writing, a method was sought to visualise and manage the writing process. This paper investigates how an Oobeya room can be implemented in construction research to support paper writing. Experiences of working with the Oobeya room in three separate research divisions prove that it is possible and fruitful to better manage knowledge in academic institutions. Even though research is creative, it can be properly managed without hampering scientific freedom. Evidence from managing scientific paper writing using the Oobeya room shows that proper management of research will actually create better research that is more publishable with shorter lead times!. Godkänd; 2012; 20130312 (andbra)